Canva Application Training in Creating Shared Flayer Designs Baitul Halim Youth (RBH) - Dwi Yuni Utami; Minda Septiani; Rangga Pebrianto; Fani Nurona Cahya (Pusat Riset dan Inovasi Nasional, 2023)
The existence of information technology is of course very helpful in all aspects of life, but the use of technology has not been fully implemented optimally. For example, Youth Members of the Baitul Halim Mosque located in Mampang, South Jakarta, who have not optimally utilized the available technology. Therefore, we plan to provide training on the use of information technology for Baitul Halim Mosque Youth Members, namely the Canva Application. This training aims to be more able to apply information technology to support daily activities in the Baitul Halim Mosque Young Members environment and to make it easier to manage data and search for data needed by Baitul Halim Mosque Youth Members there. Training activities are carried out using both online and offline methods.